Pollutant dynamics between The Black Sea and The Marmara Sea: Basis for wastewater management strategy - Orhon, D.; Sözen, S.; Kirca, V S O.; Duba, S.; Mermutlu, R.; Sumer, B M. (Elsevier BV, 2021)
The study evaluated pollutant dynamics between The Black Sea and The Marmara Sea using data collected during a marine survey of the region around The Bosphorus strait, in the last five years. A hydraulic model was utilized to define two-layered water exchange in The Bosphorus. Analysis of pollutant exchange indicated The Black Sea as major polluter for the marine environment in The Marmara Sea. Four wastewater outfalls are located along The Bosphorus; Mass balances between the two ends of The Bosphorus indicated losses of 44 t/d total N and 138 t/d COD in the lower layer before reaching The Black Sea. This was explained with a simultaneous nitrification-denitrification process sustained in the low oxygen or anoxic zones around the outfalls, implying that a sustainable wastewater strategy should preclude additional treatment for The Bosphorus discharges, since they do not have an appreciable impact on the water quality of the lower flow.
Keywords: Black Sea; Environmental Pollutants; Wastewater; Nitrification